2015
DOI: 10.1038/nclimate2683
|View full text |Cite
|
Sign up to set email alerts
|

Diatom acclimation to elevated CO2 via cAMP signalling and coordinated gene expression

Abstract: Diatoms are responsible for ∼40% of marine primary productivity 1 , fuelling the oceanic carbon cycle and contributing to natural carbon sequestration in the deep ocean 2 . Diatoms rely on energetically expensive carbon concentrating mechanisms (CCMs) to fix carbon e ciently at modern levels of CO 2 (refs 3-5). How diatoms may respond over the short and long term to rising atmospheric CO 2 remains an open question. Here we use nitrate-limited chemostats to show that the model diatom Thalassiosira pseudonana ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 38 publications
7
90
2
Order By: Relevance
“…Consistent with our finding that PtGO1 is a good candidate for the oxidation of photorespiratory glycolate, its expression was recently found to be downregulated in response to elevated CO 2 together with other genes involved in metabolizing photorespiratory glycolate (Hennon et al 2015). An analysis of transcript-level changes after induction of photorespiration in response to silicon starvation in T. pseudonana also indicated coordinately increased levels of the PtGO1 ortholog and other photorespiratory genes (Claquin et al 2002;Smith et al 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our finding that PtGO1 is a good candidate for the oxidation of photorespiratory glycolate, its expression was recently found to be downregulated in response to elevated CO 2 together with other genes involved in metabolizing photorespiratory glycolate (Hennon et al 2015). An analysis of transcript-level changes after induction of photorespiration in response to silicon starvation in T. pseudonana also indicated coordinately increased levels of the PtGO1 ortholog and other photorespiratory genes (Claquin et al 2002;Smith et al 2016).…”
Section: Discussionsupporting
confidence: 88%
“…An analysis of transcript-level changes after induction of photorespiration in response to silicon starvation in T. pseudonana also indicated coordinately increased levels of the PtGO1 ortholog and other photorespiratory genes (Claquin et al 2002;Smith et al 2016). In contrast, the PtGO2 homolog did not appear coordinately expressed with other photorespiratory genes (Hennon et al 2015;Smith et al 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 73%
“…It is difficult to extrapolate the response of individual species to natural communities, as monospecific studies exclude interactions among species and trophic levels. Estimates of CO 2 tolerance under laboratory conditions may also be influenced by experimental acclimation periods (Trimborn et al, 2014;Hennon et al, 2015;Torstensson et al, 2015;Li et al, 2017a), differences in experimental conditions (e.g. nutrients, light climate) (Hoppe et al, 2015;Hong et al, 2017;Li et al, 2017b), methods of CO 2 manipulation (Shi et al, 2009;Gattuso et al, 2010), and region-specific environmental adaptations (Schaum et al, 2012).…”
mentioning
confidence: 99%
“…Molecular-level tools that can track transcripts, proteins, or even metabolites and biochemicals in a taxon-specific way are increasingly being used in cultures and field populations to track metabolic capacity and physiological responses (16)(17)(18)(19)(20)(21)(22)(23). Molecular assessment of physiology for eukaryotic populations is most tractable in coastal systems with high biomass (17,18); thus, in oligotrophic ocean regions, molecular studies of physiology have typically been limited to the numerically abundant members of the microbial community: picoplankton (cyanobacteria, heterotrophic bacteria, and small picoeukaryotes).…”
Section: Significancementioning
confidence: 99%